An ethnobotanical analysis on wild edible plants of the turkish asteraceae taxa - (:unkn) unknown (University of Zagreb, 2019)
Asteraceae (Compositae) is one of the biggest families in the Flora of Turkey as in the World. Also, it is one of the most important families in which many popular plants are used as food and recreational tea in Turkey. The aim of this study is to make an ethnobotanical analysis on the wild edible plants of the Asteraceae family in Turkey, according to our investigations and scientific literature records. This study is based on local ethnobotanical investigations. The information about the plants was obtained from the local people through open and semi-structured interviews. In the light of our investigations and the literature records, 43 genera (including 121 taxa) of Asteraceae (used for food, tea and other purposes) were determined. Among them, Scorzonera, Tragopogon, Cirsium, Centaurea, Onopordum, Taraxacum, Echinops, Achillea, Anthemis and Carduus are the most popular genera in the localities of Turkey. © 2019, University of Zagreb. All rights reserved.
Keywords: Asteraceae; Ethnobotany; Wild edible plants Turkey